Leading across new borders : how to succeed as the center shifts - Gundling, Ernest; Caldwell, Christie, 1977- (Hoboken : Wiley, 2015)
"Leading Across Borders takes up a newer aspect of leadership that has emerged full-blown with the increasing importance of China, India, Brazil, Turkey, Indonesia, and other growing economies. Companies and their employees must now work in an environment that is more globally interconnected each day. This book draws upon deep practical experience, and fresh data to identify the distinctive challenges of leading in a global context rather than a domestic one. It provides valuable advice for anyone who is taking on a global leadership role. In addition to general differences in time zones, language, culture, institutions, and economic environments, global leaders must also typically serve more numerous stakeholders and achieve their goals in a matrix organizational structure without direct lines of authority. Leading Across Borders teaches readers to operate effectively at three levels: - Self - Team - Organization"--
The shifting center : emerging markets have emerged -- Global talent : beyond outsourcing -- Global mindset : beyond culture -- Global teams : beyond facilitation -- Global inclusion : beyond race and gender -- Global mergers and acquisitions : beyond diligence -- Global innovation : beyond products -- Global ethics : beyond integrity -- Leading from your own center.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Leadership; International business enterprises; Leadership; Entreprises multinationales; BUSINESS & ECONOMICS -- Leadership; International business enterprises; Leadership